Association of TP53 codon 72 and CDH1 genetic polymorphisms with colorectal cancer risk in Bangladeshi population. (August 2017) - Rivu, Sanzana Fareen; Apu, Mohd Nazmul Hasan; Shabnaz, Samia; Nahid, Noor Ahmed; Islam, Md. Reazul; Al-Mamun, Mir Md. Abdullah; Nahar, Zabun; Rabbi, Sikder Nahidul Islam; Ahmed, Maizbha Uddin; Islam, Mohammad Safiqul; Hasnat, Abul
Highlights: This is the first case-control study ever conducted on Bangladeshi colorectal cancer patients in terms of TP53 codon 72 and CDH1 genetic polymorphisms. Arg/Pro heterozygosity and Pro/Pro mutant homozygosity at codon 72 of TP53 shows a significant association for colorectal cancer predisposition. A allele and combined genotype of C/A and A/A of CDH1 represent an elevated risk of colorectal cancer development. Abstract: Till now no pharmacogenetic study of TP53 codon 72 (Arg72Pro) and CDH1 rs16260 (-160C<A) genes has been reported on Bangladeshi population relating those with colorectal cancer. So the aim of the study is to determine whether there is an elevated risk of colorectal cancer development with TP53 codon 72 and CDH1 rs16260 genetic polymorphism in Bangladeshi population for the first time. To investigate the association of these two SNPs, we conducted a case-control study with 288 colorectal cancer patients and 295 healthy volunteers by using polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP) method. We found an increased risk of association between Arg/Pro heterozygosity (adjusted OR = 2.58, 95% CI = 1.77–3.77, p < 0.05) and Pro/Pro mutant homozygosity (adjusted OR = 2.92, 95% CI = 1.78–4.78, p < 0.05) along with the combined genotype (Arg/Pro + Pro/Pro) (adjusted OR = 2.70, 95% CI = 1.90–3.82, p < 0.05) and colorectal cancer predisposition. In case of CDH1 rs16260 polymorphism, C/A heterozygous and A/A mutant homozygous are significantly (p < 0.05) found to be associated with colorectal cancer risk with adjusted OR of 1.94 and 2.63, respectively. The combined genotype of C/A and A/A was also found to be strongly associated with colorectal cancer risk compared to C/C genotype (adjusted OR = 2.02, 95% CI = 1.42–2.87, p < 0.05). In conclusion, heterozygosity and mutant homozygosity as well as the combination of both TP53 Arg72Pro and CDH1 rs16260 polymorphisms are responsible to increase the risk of colorectal cancer development in Bangladeshi population.